The Impact of Covid-19 on Islamic Economics and Finance Industry: Text Analytics using R - Aam Slamet Rusydiana; Evania Herindar; Nisful Laila (Global Review of Islamic Economics and Business, 2021)
Covid-19 not only has an impact on the financial industry but also generally affected on the world economy. In the financial industry, currently, Islamic finance is growing fast. Thus, this study aims to determine the development of research on the impact of Covid-19 on the economy and the Islamic finance industry in the world by analyzing a study of 47 documents from the 2020-2021 period on the Scopus database using text analysis using R-studio. This study provides an analysis of keywords that are often used in the topic and provides an overview of the analysis of the most relevant words, word treemaps, co-occurrence networks, thematic maps, and conceptual structures. The results of this study indicate that Covid-19 has harmed several sectors of the Islamic economy and finance, including Islamic banking, Islamic capital markets, Islamic microfinance institutions, and tourism. In addition, the results of this study also provide several recommendations for several industries that have been negatively affected by the Covid-19 pandemic.